2014
DOI: 10.2147/jhc.s71602
|View full text |Cite
|
Sign up to set email alerts
|

Chemoembolization with drug-eluting microspheres (DEM-TACE) for hepatocellular carcinoma: single-center review of safety and efficacy

Abstract: PurposeThis study examines the safety and efficacy of transarterial chemoembolization using doxorubicin-loaded 30–60 µm QuadraSphere microspheres (DEM-TACE) for the treatment of hepatocellular carcinoma.Materials and methodsOver 10 weeks, patients with hepatocellular carcinoma. (Child–Pugh A/B: 65%/35%) were embolized with 30–60 µm QuadraSphere microspheres. Excluded patients had previous locoregional therapy, macrovascular invasion, extrahepatic disease, Child–Pugh score >B7, ECOG performance status >0, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…So far, Hepasphere with a size of 30-60 μm has been marketed, and several studies have examined the efficacy and safety. 56,57 The Child-Pugh score is a well-known prognostic factor for HCC, 58,59 and we found that OS was significantly shorter in patients with a Child-Pugh score of ≥8 than in patients with a score of 5-7. This suggests that patients with a Child-Pugh score of ≤7 may experience a greater benefit of this treatment strategy.…”
mentioning
confidence: 67%
“…So far, Hepasphere with a size of 30-60 μm has been marketed, and several studies have examined the efficacy and safety. 56,57 The Child-Pugh score is a well-known prognostic factor for HCC, 58,59 and we found that OS was significantly shorter in patients with a Child-Pugh score of ≥8 than in patients with a score of 5-7. This suggests that patients with a Child-Pugh score of ≤7 may experience a greater benefit of this treatment strategy.…”
mentioning
confidence: 67%
“…If IPSO microdroplets are too small for the inner diameter of the tumor vasculature, they may pass through the tumor tissues and normal tissues; if the microdroplets are too large, they are trapped proximal to the tumor vasculature (15,16). Drug-eluting beads (DEBs) have been developed for transcatheter treatment of HCC because DEBs can deliver higher dose of the anticancer agents and prolong the contact time with the tumor (17)(18)(19)(20)(21). Treatment with DEBs reduces the amount of anticancer agent reaching the systemic circulation (18).…”
Section: Discussionmentioning
confidence: 99%
“…TACE is the standard curative treatment and is a well-established procedure for patients with unresectable HCC, according to the Barcelona Clinic Liver Cancer (BCLC) algorithm. ,, In addition, TACE has also been used for metastatic neuroendocrine liver metastases as a palliative treatment . This procedure offers a high dose of chemotherapeutic agents to the tumor tissue while preserving the surrounding normal hepatic parenchyma .…”
Section: Non-radioactive Microspheresmentioning
confidence: 99%
“…In addition, the smaller caliber microspheres (<100 μm) provided better outcomes without influencing patient safety . These drug-eluting microspheres offered advantages in highly spherical and smaller sizes compared to microbeads, resulting in higher treatment efficacy and decreased fatigue . Thus, drug-eluting microspheres could increase the distal penetration and embolization of target tissue, decreasing postembolization syndromes .…”
Section: Non-radioactive Microspheresmentioning
confidence: 99%
See 1 more Smart Citation